Gamification activities to enhance reading skills intenthgradee students from “San Antonio of Padua” school during the period 2020-2021 - Acosta Guzmán, María Oliva (2023)
To propose the appropriate gamifica tion activities to enhance the r eading skill of tenth grade students from the San Antonio de Padua School during the year 2020 2021.